Microorganisms and dietary factors affecting biohydrogenation and conjugated linoleic acid production in the rumen ecosystem - Maia, Margarida Rosa Garcez (2011)
Tese de Doutoramento em Ciências Veterinárias, especialidade de Produção Animal